Dissimilarity and Ambiguity in Ukrainian and English Cybersecurity Terminology - Venkel, Tetiana V.; Maniutina, Olena; Zeluk, Andriy ("Рута", Чернівці, 2021)
The problem of ambiguity of definitions and dissimilarities in the cybersecurity terminology of the Ukrainian and English languages is considered in the paper. Due to its rapid development and continuous completion with new terms, the cyber-terminology demonstrates lack of ordering and proper study. The general analysis of the state of affairs in this field showed the prevalence of borrowings from the English language, mostly represented in Ukrainian by means of transcription/transliteration, loan translation, equivalents or analogies, which still may require additional explanations. Synonymy and antonymy in the terminological system of cybersecurity are also detected, represented generally by the borrowed and proper Ukrainian terms. The definitions of the cyber-terms can differ significantly in English and Ukrainian or are sometimes unclear and ambiguous causing misinterpretation. Thus, it is necessary to define a unified, understandable and well-ordered terminological system of cybersecurity in the Ukrainian language
Keywords: cybersecurity terminology, cyberspace, conceptual framework of the language, cyber-aware society